A Mixed Course-Based Research Approach to Human Physiology - Haen Whitmer, Karri (Open textbook library., 2021)
The Biology 256 Laboratory course was designed to provide students with hands-on access to modern techniques in human physiological analyses using the course-based research pedagogical approach. In this course, students will learn how to perform literature searches; generate research questions and hypotheses; design experiments; collect, analyze, visualize and interpret data; and present scientific findings to others. The Biol 256L curriculum offers a high-impact human physiology experience that fosters the critical thinking skills required to be a successful citizen in a modern world filled with misinformation.